MEKANISME PENERBITAN PERPPU NOMOR 1 TAHUN 2013 TENTANG PERUBAHAN KEDUA ATAS UU NOMOR 24 TAHUN 2003 TENTANG MAHKAMAH KONSTITUSI DALAM KAIDAH KEGETINGAN YANG MEMAKSA - Fernando Silalahi (to-ra, 2019)
Abstract Indonesian President Susilo Bambang Yudhoyono signed Government Regulation in Lieu of Law No. 1 of 2013 concerning the Second Amendment to Law No.24 of 2003 concerning the Constitutional Court, which was an-nounced by Coordinating Minister for Political, Legal and Security Affairs (Menkopolhukam) Djoko Suyanto, in Gedung Agung Yogyakarta on October 17, 2013 Special Region of Yogyakarta (DIY). After the previous Saturday, October 5, 2013, the President met with leaders of state institutions at the State Palace. The meeting recommended ve agendas and steps to save the Constitutional Court (MK), and was announced directly by the PresidentKeyword: government regulation; second amendment; constitutional court